Analysis of Acoustic Absorption Coefficients and Characterization of Epoxy Adhesive Compositions Based on the Reaction Product of Bisphenol A with Epichlorohydrin Modified with Fillers - Miturska-Barańska, Izabela; Rudawska, Anna; Sobotova, Lydia; Badida, Miroslav; Olewnik-Kruszkowska, Ewa; Müller, Miroslav; Hromasová, Monika (Materials, 2024)
Material development in acoustic engineering plays a significant role in various applications, such as industrial noise control. It is important and relevant to consider alternative materials capable of reducing noise levels in different frequency ranges. One commonly used material in engineering structures is epoxy adhesive compositions. Favoring the use of adhesive compositions are their main characteristics, including weight reduction in structures, corrosion resistance, relatively low manufacturing costs, and high mechanical strength. This paper aims to discuss the relationship between the mechanical properties of modified epoxy adhesives, their structure, and sound absorption efficiency. The subjects of this study were specimens of an epoxy composition in the cured state. Acoustic absorption coefficients were evaluated using a dual-microphone impedance tube, and tensile, compressive, and bending strength properties were determined using a testing machine. The impact strength of the compositions was also investigated. An analysis of the structure of the adhesives in the cured state was carried out using a scanning electron microscope. The test specimens were made from Epidian 5 epoxy resin cured with a polyamide PAC curing agent. Nanobent ZR2 aluminosilicate in an amount of 1%, CaCO3 calcium carbonate in an amount of 5%, and CWZ-22 activated carbon in an amount of 20% were used as modifiers. The conducted studies revealed that the highest tensile strength was obtained for the adhesive composition with the addition of ZR2 filler. The highest compressive strength was exhibited by the adhesive composition with the addition of CWZ-22 filler. The highest flexural strength was demonstrated by the unmodified composition. For all the tested adhesive compositions, low sound absorption values were achieved, with a maximum of approximately 0.18. From the perspective of the reduction index R, it was observed that these samples performed better in reduction than in absorption. The best values were achieved in the compositions modified with CaCO3.